2019
DOI: 10.1002/asia.201900968
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Mediated O‐Arylation of Alcohols and Phenols by Triarylsulfonium Triflates

Abstract: A mild and efficient protocol for O‐arylation of alcohols and phenols (ROH) by triarylsulfonium triflates was developed under transition‐metal‐free conditions. Various alcohols, including primary, secondary and tertiary, and phenols bearing either electron‐donating or electron‐withdrawing groups on the aryl rings were smoothly converted to form the corresponding aromatic ethers in moderate to excellent yields. The reactions were conducted at 50 or 80 °C for 24 h in the presence of a certain base and showed goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…5,10 In addition, sulfoniums bearing electron-deficient aryl substituents were also synthesized and used for the O-arylation presented here. Unlike previously reported O-arylation reactions using acyclic triarylsulfoniums, 7 an exocyclic aryl group on sulfur of a phenothiazine ring was selectively introduced. This unique selectivity was also supported by theoretical calculations.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…5,10 In addition, sulfoniums bearing electron-deficient aryl substituents were also synthesized and used for the O-arylation presented here. Unlike previously reported O-arylation reactions using acyclic triarylsulfoniums, 7 an exocyclic aryl group on sulfur of a phenothiazine ring was selectively introduced. This unique selectivity was also supported by theoretical calculations.…”
mentioning
confidence: 68%
“…When Sphenylthianthrenium was used, the corresponding reactions were reported to be competitive. 7 In contrast, our experimental results showed that the reaction using S-arylphenothiazinium proceeded selectively in path A. The observed selectivity was investigated using DFT calculations at the B3LYP/6-311G +(d,p) level.…”
mentioning
confidence: 99%
“…PdCl2 was obtained from FUJIFILM Wako Pure Chemical Corporation. Phenyl thiophene-2-carboxylate (1A), [1] phenyl thiophene-3-carboxylate (1B), [1] phenyl furan-2-carboxylate (1C), [1] phenyl oxazole-4-carboxylate (1D), [2] phenyl picolinate (1E), [1] phenyl isonicotinate (1F), [1] phenyl pyrazine-2-carboxylate (1H), [1] phenyl isoquinoline-1-carboxylate (1J), [3] phenyl 2-phenylquinoline-4-carboxylate (1L), [1] phenyl 4-methylbenzoate (1M), [4] phenyl 1-naphthoate (1N), [5] phenyl 6-methoxy-2-naphthoate (1O), [5] phenyl anthracene-2-carboxylate (1P), [6] phenyl [1,1'-biphenyl]-2-carboxylate (1Q), [5] phenyl [1,1'-biphenyl]-4-carboxylate (1R), [5] phenyl 4'-(tert-butyl)-[1,1'-biphenyl]-4-carboxylate (1S), [7] phenyl 4-methoxybenzoate (1T), [4] phenyl benzo[d] [1,3]dioxole-5-carboxylate (1U), [5] phenyl 4-(trifluoromethoxy)benzoate (1V), [8] phenyl 4-(trifluoromethyl)benzoate (1W), [4] phenyl 4-cyanobenzoate (1Y), [4] phenyl 3-(dimethylamino)benzoate (1Z), [5] phenyl 4-vinylbenzoate (1AA), [9] phenyl 4-acetylbenzoate (1AB), [10] methyl phenyl terephthalate (1AC), [5] phenyl 4-(N,N-dipropylsulfamoyl)benzoate (1AI), [6] [2] methyl thiophene-2-carboxylate (5A), [11] thiophene-2-carbaldehyde (5B), [12] 4-(trifluoromethyl)phenyl thiophene-2-carboxylate (5C), [13] phenyl thiophene-2-carbothioate (5E), [14] and 2-(phenoxymethyl)thiophene (5F) [15] were synthesized according to procedures and the spectra matched with those of compounds reported in the literature.…”
Section: Generalmentioning
confidence: 99%
“…the ligand was changed from dcypt to various phosphine ligands,the highest yield of 3A was obtained (89% yield) without any decarbonylative product 4A (using dcype, Table 1, entries [8][9][10][11][12][13][14][15][16]. It should be noted that the reaction hardly proceeds without the Pd metal or the ligand (Table 1, entries 17 and 18).…”
mentioning
confidence: 99%
“…Alcohols are abundant, cheap, environmentally benign, easily accessible, and frequently used raw materials in organic synthesis . The combination of alcohols with fluorination and fluoroalkylation reagents has constructed a large number of useful fluorine-containing molecules .…”
mentioning
confidence: 99%